1079 Analysis of Human Papilloma Virus (HPV) Status in Metastatic Oropharyngeal Squamous Cell Carcinoma (OPSCC). (12th October 2021) - Kathiravelupillai, A; Arora, A; Jeannon, J P; Brunet-Garcia, A; Faulkner, J; Sandison, A
Abstract: Introduction: OPSCC often (80%) presents with ipsilateral neck metastasis. Presentation may be as carcinoma of unknown primary (CUP). Sampling via ultrasound guided Fine Needle Aspiration Cytology (FNAC) and/or Core Biopsy (CB) from nodal metastases is required for diagnosis, comparison with primary tumour and to assess human papilloma virus (HPV) status. HPV positive biopsy from CUP may indicate oropharynx primary. HPV positive OPSCC has better prognosis. HPV association is ascertained by p16 immunocytochemistry (p16- IHC) and HPV DNA in situ hybridization (HPV-ISH). In a cohort of OPSCC patients from a single referral centre 68% had metastatic disease. Core biopsy was optimal for HPV testing. Method: Retrospective review of records from Transoral Robotic Surgery (TORS) patients treated for OPSCC between December 2017-2019 was conducted. Cohort included patients undergoing TORS for diagnostic purposes and with curative intent. Results: Data was available from 23 patients who had TORS for OPSCC. 47.8% (n = 11) presented with lymphadenopathy. 82.6% (n = 19) underwent FNAC. 68.4% (n = 13) were diagnosed with metastatic OPSCC and 56.5% (n = 13) underwent neck dissections. 52.2% (n = 12) had confirmed HPV positive metastases, 75% (n = 9) had 1 node positive, 25% (n = 3) had >1 node positive. FNAC yielded enough tissue for p16 IHC and HPV-ISH in 10.5% (n = 2). CB yielded sufficient tissue for analysis in all cases 39.1% (n = 9). Conclusions: The study confirms high incidence of neck metastases in HPV associated OPSCC patients. Needle core biopsy appears superior to FNAC for tissue sampling to assess HPV status in tumours metastatic to neck.